A Production systems study on Jollibee Foods Corporation - Baritugo, Jean Paul; Catanghal, Elena; Legaspi, Ma. Theresa; Umali, Honorio Jr; Yu, Lawrence (College of Engineering, 1993)
This study aimed at using the techniques of operations management in a real life system. Specifically, queueing analysis and the principles and techniques of facility lay-outing were used to address the company's specific problems. Preliminary investigation of the existing system was conducted to determine the various problems and management concerns of the company. Subsequent visits were made for data gathering and research to come up with the detailed analysis of these problems and their respective solutions. The store's limited facility (i.e., dining area) constitutes its core problem. Because of this, unrealized profit from untapped markets and the under-utilization of facilities crop up. The team then formulated a solution that would maximize sitting capacity for the proposed expansion and determined the number of personnel needed to accomplish added tasks within a specified quality level. The team was faced with numerous constraints that prevented it from using most of the techniques learned from IE 151. Data such as costs, sales of product, and demand were not given to the group, hence, forecasting, inventory management and other analytical tools were not used. However, the company reported that they do not experience any problems with the other aspects (i.e., finance, marketing, etc.) addressed by these tools except for their capacity. Hence, the discussion, analysis and recommendations of this paper are simply what is needed and appropriate.